Learning Media Development Using Educandy Games to Improve Digital Literacy of Grade V Students of Citra Bangsa Kupang Christian Elementary School - Mole, Ronald; Sogen, Maria M.B.; Fallo, Diana Y. A. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Ronald Mole: Development of Learning Media Using Educandy Game to Improve Digital Literacy of Grade V Students of Citra Bangsa Christian Elementary School Kupang. This research uses the ADDIE model in making games which consists of 5 steps, namely the stages (Analysis) Analysis, (Design) Design, (Develop) Development, (Implement) Implementation, and (Evaluate) Evaluation where this research produces learning media in the form of games with the Educandy application which consists of 5 games, namely:  Noughts & Crosses, Crosswords, Match-up, Memory, and Multiple Choise which were developed by each fifth grade student of Citra Bangsa Kupang Christian Elementary School and proven to be effective in increasing students' digital literacy with a very feasible category. The use of learning media with Educady Application to improve digital literacy shows that the games made by researchers are effective to use with a final score of 87% and a very feasible level of achievement as ICT learning media in improving digital literacy of grade V students of Citra Bangsa Kupang Christian Elementary School. Educandy as a means of making test instruments that are very suitable for the development of this all-digital era has proven to be able to encourage the development of literacy of fifth grade students of Citra Bangsa Christian Elementary School.